Profiling and integrated analysis of differentially expressed circRNAs as novel biomarkers for breast cancer. Issue 11 (14th January 2020) - Li, Zehuan; Chen, Zhanghan; Hu, Guohua; Zhang, Yong; Feng, Yanling; Jiang, Ying; Wang, Jin
Abstract: Breast cancer (BC) is a globally common cancer with the highest and increasing morbidity and mortality among females. Novel biomarkers are warranted to be discovered for the early detection, treatment, and prognosis of BC. In this study, we investigated the profiles of differentially expressed (DE) circular RNAs (circRNAs) by competing endogenous RNAs (ceRNA) microarray to construct a genome‐wide circRNA profile. Then, we performed Gene Ontology (GO) analysis and Kyoto Encyclopedia of Gene and Genome (KEGG) pathway analysis of the host genes (HGs) of circRNAs. A total of 4, 370 DE circRNAs were detected and GO and KEGG analysis showed that they were significantly associated with cell cycle, DNA replication, BC, and familial BC. We validated the differential circRNAs and relevant HGs through quantitative real‐time polymerase chain reaction and constructed a putative circRNA–microRNA–messenger RNA regulatory network. Eight circRNAs, including hsa_circ_0069094, hsa_circ_0062558, hsa_circ_0074026, hsa_circ_0079876, hsa_circ_0017536, hsa_circ_0023302, hsa_circ_0017650, and hsa_circ_0017545, were validated significantly DE in BC tissue and associated with TNM staging, lymph node infiltration, and Ki67. Hsa_circ_0069094, hsa_circ_0079876, hsa_circ_0017650, and hsa_circ_0017526 were upregulated in plasma. This study revealed the general expression characteristics of specific DE circRNAs in BC and hsa_circ_0069094, hsa_circ_0079876, hsa_circ_0017650, and hsa_circ_0017526 might be promising candidate targets. Abstract : We constructed the general profiling of specific differentially expressed (DE) circular RNAs (circRNAs) in human breast cancer (BC) through competing endogenous RNA (ceRNA) microarray. Also, we validated the differential circRNAs through quantitative real‐time polymerase chain reaction (qRT‐PCR) both in tissue and plasma, as well as used network analysis and clinical feature correlation analysis to reveal these circRNAs and their host genes as candidate targets for BC.